Answer:
(16x + 21) and (16x - 6)
Step-by-step explanation:
f(g(x)) = f(6 + 4x)
Applying the f(x) function on (6 + 4x) gives
4(6 + 4x) - 3
Which equals 16x + 24 - 3
= 16x + 21
g(f(x)) = g(4x - 3)
Applying the g(x) function on (4x - 3) gives
6 + 4(4x - 3)
Which equals 6 + 16x - 12
= 16x - 6
Answer:
F or H
Step-by-step explanation:
not J because that is negative, not G because that means none, so either H or F. I'm not going to give you the whole answer but another hint is look at the circles are they circled or non circlircled. I eliminated two answers for you.
remember what your teachers saids: what does it mean for the circlies to be colored or blank.
good luck!
Answer:
3
Step-by-step explanation:
-m+8=4m-7
8=4m-(-m)-7
8=4m+m-7
8=5m-7
5m=8+7
5m=15
m=15/5
m=3
Answer: Graph B and Graph D